Study on the Degradation Pattern of Impact Crater Populations in Yutu-2′s Rovering Area - Xinyu Ma; Meixi Chen; Teng Hu; Zhizhong Kang; Meng Xiao (Remote Sensing, 2024)
A detailed analysis of the panoramic camera data from the 27th to 33rd lunar days was conducted on the high-resolution scenes captured by the Yutu-2 rover stations. This analysis aimed to determine the detailed morphological parameters of the 2015 impact craters within the inspection area. The levels of degradation observed in the impact craters were determined alongside the surface features. Subsequently, the degradation patterns of the impact craters located within the Yutu-2’s roving area and the distribution patterns of the morphological parameters were analysed and investigated. The results of the analysis indicate that 94% of the impact craters exhibited severe degradation, 80% had depth-to-diameter ratios (DDRs) ranging from 0.07 to 0.17, and the remaining craters were moderately degraded. The DDRs of the impact craters exhibited a declining trend with an increase in the dimensions of the impact craters. Additionally, the degree of degradation of impact crater populations demonstrated a decreasing trend. In general, the impact craters along the rover’s route exhibited severe degradation, with the population of degradation degrees gradually decreasing with increasing diameter.